The role of photospheric converging motion in initiation of solar eruptions - Bian, Xinkai; Jiang, Chaowei; Feng, Xueshang (Frontiers in Astronomy and Space Sciences, 2022)
It is well known that major solar eruptions are often produced by active regions with continual photospheric shearing and converging motions. Here, through high accuracy magnetohydrodynamics simulation, we show how solar eruption is initiated in a single bipolar configuration as driven by first shearing and then converging motions at the bottom surface. Different from many previous simulations, we applied the converging motion without magnetic diffusion, thus it only increases the magnetic gradient across the polarity inversion line but without magnetic flux cancellation. The converging motion at the footpoints of the sheared arcade creates a current sheet in a quasi-static way, and the eruption is triggered by magnetic reconnection of the current sheet, which supports the same scenario as shown in our previous simulation with only shearing motion. With the converging motion, the current sheet is formed at a lower height and has a higher current density \textcolor{blue}{than with shearing motion alone}, which makes reconnection more effective and eruption stronger. Moreover, the converging motion renders a fast decay rate of the overlying field with height and thus favorable for an eruption. This demonstrate that the converging flow is more efficient to create the current sheet and more favorable for eruption than by solely the shearing flow.